1999
DOI: 10.1103/physrevb.60.r8422
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of the Mott insulating ground state ofCa2RuO4by a structural transition

Abstract: We report a first-order phase transition at T M =357 K in single crystal Ca 2 RuO 4 , an isomorph to the superconductor Sr 2 RuO 4 . The discontinuous decrease in electrical resistivity signals the near destruction of the Mott insulating phase and is triggered by a structural transition from the low temperature orthorhombic to a high temperature tetragonal phase. The magnetic susceptibility, which is temperature dependent but not Curie-like decreases abruptly at T M and becomes less temperature dependent. Unli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
124
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(135 citation statements)
references
References 26 publications
11
124
0
Order By: Relevance
“…A common characteristic of these materials is that underlying physical properties are critically linked to the lattice and orbital degrees of freedom and tend to exhibit a giant response to modest lattice changes. This is dramatically illustrated by Sr 2 RuO 4 and Ca 2 RuO 4 , where the former compound exhibits a prototypical p-wave superconducting state [1] that strongly contrasts with the more distorted structure (due to a smaller ionic radius r Ca < r Sr ) and first-order metal-insulator transition, T MI , observed for the latter compound [2,3].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A common characteristic of these materials is that underlying physical properties are critically linked to the lattice and orbital degrees of freedom and tend to exhibit a giant response to modest lattice changes. This is dramatically illustrated by Sr 2 RuO 4 and Ca 2 RuO 4 , where the former compound exhibits a prototypical p-wave superconducting state [1] that strongly contrasts with the more distorted structure (due to a smaller ionic radius r Ca < r Sr ) and first-order metal-insulator transition, T MI , observed for the latter compound [2,3].…”
Section: Introductionmentioning
confidence: 98%
“…Classic Mott insulators undergo simultaneous transitions to antiferromagnetic (AFM) order and an insulating state at T MI . However, Ca 2 RuO 4 undergoes AFM order at T N = 110 K T MI , [2] and is therefore a highly interesting and unique archetype of a metal-insulator transition that is strongly coupled to a structural transition from a high-T tetragonal to low-T orthorhombic distortion and is not driven by AFM exchange interactions [2,3,6,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, there exists many sophisticated situations rather than an ideal situation to be explained simply. For instance, the layered perovskite Ca 2 RuO 4 has shown the orbital selective Metal-insulator transition [6,7,8]. In Sr 2 IrO 4 , it has been reported that Mott insulator develops due to the strong spin-orbit interaction of Ir 5d-electrons [9].…”
Section: Introductionmentioning
confidence: 99%
“…At ambient pressure, this material is a Mott insulator which orders antiferromagnetically at T N = 110 K. At higher temperatures, Ca 2 RuO 4 goes through a structural phase transition at 357 K, from S-Pbca, where the octahedra is tilted and rotated, with a shortened c-axis, to LPbca type of structure in which the c-axis becomes elongated. This transition, in turn, induces a metal-insulator transition 3 .…”
Section: Introductionmentioning
confidence: 99%